SURFACE STRUCTURE EFFECTS ON DIRECT REDUCTION OF IRON OXIDES BY SHEWANELLA ONEIDENSIS - Neal A.L.; Rosso K.M.; Geesey G.G.; Gorby Y.A.; Little B.J. (My University, 2003)
The atomic and electronic structure of mineral surfaces affects many environmentally important processes such as adsorption phenomena. They are however rarely considered relevant to dissimilatory bacterial reduction of iron and manganese minerals. In this regard, surface area and thermodynamics are more commonly considered. Here we take a first step towards understanding the nature of the influence of mineral surface structure upon the rate of electron transfer from Shewanella oneidensis strain MR-1 outer membrane proteins to the mineral surface and the subsequent effect upon cell ''activity.'' Cell accumulation has been used as a proxy for cell activity at three iron oxide single crystal faces; hematite (001), magnetite (111) and magnetite (100). Clear differences in cell accumulation at, and release from the surfaces are observed, with significantly more cells accumulating at hematite (001) compared to either magnetite face whilst relatively more cells are released into the overlying aqueous phase from the two magnetite faces than hematite. Modeling of the electron transfer process to the different mineral surfaces from a decaheme (protoporphyrin rings containing a central hexacoordinate iron atom), outer membrane-bound cytochrome of S. oneidensis has been accomplished by employing both Marcus and ab initio density functional theories. The resultant model of electron transfer to the three oxide faces predicts that over the entire range of expected electron transfer distances the highest electron transfer rates occur at the hematite (001) surface, mirroring the observed cell accumulation data. Electron transfer rates to either of the two magnetite surfaces are slower, with magnetite (111) slower than hematite (001) by approximately two orders of magnitude. A lack of knowledge regarding the structural details of the heme-mineral interface, especially in regards to atomic distances and relative orientations of hemes and surface iron atoms and the conformation of the protein envelope, precludes a more thorough analysis. However, the results of the modeling concur with the empirical observation that mineral surface structure has a clear influence on mineral surface-associated cell activity. Thus surface structure effects must be accounted for in future studies of cell-mineral interactions.